Pola Asuh Orangtua Dalam Membentuk Karakter Anak Usia Dini - Retno Risti Darmawanti (Institut Agama Islam Negeri Metro, 2023)
One of the main factors for the success of education is the parenting style of parents, therefore parents must show more parenting style given to children to form character from an early age, so that after the child grows up, he will grow into a human being with the expected character. Furthermore, the link between parenting styles and forming early childhood character is meant as an effort by parents to lay the foundations of character in children, children who are instilled with character from an early age will have self-regulation based on religious values, cultural values, social rules, outlook on life, and an attitude of life that is meaningful for himself, society, nation and state. This type of research is qualitative and descriptive in nature. This study uses interview data collection techniques, observation and documentation. The results of this study indicate that children have begun to be able to speak politely and behave well to everyone, have a religious attitude, are independent, not selfish, respect others, and are disciplined in everyday life.